Estudo andrológico e ultrassonagráfico em carneiros durante o curso de infecção experimental por Brucella Ovis - Custódio Antônio Carvalho Júnior (2010)
Brucella ovis is considered the most important infectious cause of reproductive disorders in sheep. The disease is characterized by epididymitis, sub-fertility and infertility in rams and occasionally abortion in ewes. Although clinical aspects of the disease have been studied, changes in the parenchyma of affected organs have only been evaluated by histology, and the correlations between clinical signs and seminal features of the affected rams have been described mostly in naturally infected rams, when it is not possible to assess the time course of infection. Moreover, real-time ultrasonography has proved to be a valuable tool for studying the physiology and pathology of the male reproductive system of several species including sheep. Considering the few studies evaluating the kinetics of disease during infection with B. ovis in known time-points post infection, and the correlation of ultrasonographic changes in the parenchyma of the organs of the genital tract of sheep with seminal parameters and histological findings in these organs was evaluated in this study aiming to assess the kinetics of changes in rams experimentally infected with B. ovis. Nine rams were infected with 2 mL of 1.2 x 109 CFU/mL of B. ovis strain ATCC25840 intraprepucially, and 50 mL of a suspension containing 1.2 x 1010 CFU of the same strain in both conjunctival sacs. Six out of nine infected rams developed clinical changes in the tail of the epididymis 30 days after inoculation, but these changes regressed in 50% of these rams. The ultrasound demonstrated an increase in area of the tail of the epididymis (p<0.001), reduction in the area of the testes (p<0.001), and an increased length and depth of the seminal vesicles (p<0.001). Microscopically, there was epididymitis, testicular degeneration, and vesiculitis that confirmed the clinical and ultrasonographic findings. Changes in the echogenicity were found tail of the epididymis of one of the rams, where there was an anechoic nodule that was subsequently confirmed to be a sperm granuloma based on histology. Inflammatory cells were found in semen of symptomatic rams even before the development of epididymitis as well as in asymptomatic rams, indicating that the presence of leukocytes in the ejaculate is a valuable method for screening potential carriers of infections in the genital tract.